Exploring the parameter for alternating current electrophoretic deposition of carbon nanotubes-polyaniline: a review / Affycilla Adries and Intan Syaffinazzilla Zaine - Adries, Affycilla; Zaine, Intan Syaffinazzilla (2020)
CNTs-based materials have attracted many attentions for their outstanding chemical properties such as tensile strength and electrical conductivity. The CNTs-based materials can be deposited either using DC-EPD and AC-EPD techniques. This review specifically discusses the important parameter for alternating current electrophoretic deposition of CNTs – PANi. The information related to this review is obtained from previous studies from year 2000 to 2020. The parameter for AC-EPD can be categorized into two which are parameter related to suspension and parameter related to AC-EPD process. Both category of parameter can affect the uniformity of the dispersion of CNTs. Based on previous studies, a uniform and homogenous CNTs dispersion can be obtained by using electric field more than 20 V cm-1, peak to peak voltage in range of 0.5 V to 40 V, 300 nm distance between plate and 30 minutes or lower deposition time. Sinusoidal waveform with duty cycle of 80% can be used to deposit the CNTs as these properties are commonly used for AC-EPD. The frequency for deposition of CNTs mostly used is below 50 Hz.